Penerjemahan Kosakata Budaya pada Naskah Kumpulan Tradisi Lisan Sumatra Utara ke dalam Bahasa Jepang. - Arfandy Arya Nalle Purwoko; Althaf Gauhar Auliawan (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study aims to develop a book of oral stories from the traditions of the people of North Sumatra and translate it into Japanese while maintaining the cultural meaning and local nuances. The method used is descriptive qualitative with data collection methods in the form of text analysis and interviews with resource persons who understand traditional stories. Validation was conducted by cultural and linguistic experts to assess the accuracy, readability and cultural context appropriateness of the translations. The translation strategies analyzed refer to Inou and Kawahara's classification, which includes proposition preservation, paraphrasing, deletion, and addition. The results show that these strategies are effective in preserving cultural meaning, especially when combined with contextual adjustments and the use of footnotes. The findings confirm that translating traditional stories requires a strategic approach and continuous validation to maintain the quality and acceptability of the final product. The study concludes that the implementation of appropriate strategies not only aids the preservation of oral traditions in written form, but also expands global access to Indonesia's rich culture, particularly through translation into Japanese languages.